2020
DOI: 10.1002/jac5.1294
|View full text |Cite
|
Sign up to set email alerts
|

Observations from a systematic review of pharmacist‐led research in solid organ transplantation: An opinion paper of the American College of Clinical Pharmacy Immunology/Transplantation Practice and Research Network

Abstract: Introduction The contributions of transplant pharmacists to clinical and translational research in the United States are ill‐defined and have not been systematically reviewed. Objectives The American College of Clinical Pharmacy Immunology/Transplantation Practice and Research Network conducted a systematic review of available pharmacist‐led research publications involving solid organ transplantation with the intent to quantify and describe pharmacist‐led research endeavors and their changes over time. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Obtainment of primary research project publication during training was higher in those that went on to achieve ECP (ECP 64% [16/25] vs no ECP 36% [9/25]; P = 0.006). Additionally, the median total number of publications during postgraduate training was higher in those who accomplished ECP (3.5 2‐5 vs 2, 2 P = 0.03).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Obtainment of primary research project publication during training was higher in those that went on to achieve ECP (ECP 64% [16/25] vs no ECP 36% [9/25]; P = 0.006). Additionally, the median total number of publications during postgraduate training was higher in those who accomplished ECP (3.5 2‐5 vs 2, 2 P = 0.03).…”
Section: Resultsmentioning
confidence: 93%
“…Importantly, representation of SOT pharmacists in research publications is increasing. A systematic review of SOT‐related research publications with one or more pharmacists from 1975 to 2017 was conducted 3 . First author (87%) and senior author (67%) positions were common for pharmacists, and many of the publications included multiple pharmacist coauthors (71%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All PGY2‐trained pharmacy specialists have integral roles in advancing the profession through literature contributions. For SOT specifically, this was recently shown in a systematic review of SOT pharmacist contributions to the literature, which identified 547 SOT publications for which pharmacists served in key authorship positions; 87% and 67% as first or senior author, respectively 5 . Given the important contributions that SOT pharmacists make to the discipline, it is important to identify both barriers and facilitators for the publication of PGY2 SOT resident projects.…”
Section: Introductionmentioning
confidence: 99%